Ethnosocial processes in Siberia: modern reality and actual issues of ethnosocial policies - Popkov, Yuri V.; Tyugashev, Evgenii A. (The New Research of Tuva, 2014)
Article evaluates the dynamics in contemporary ethnosocial processes in Siberia as well as efficiency of national policies. Sociocultural approach helps in analyzing ethnodemographic, ethnolingual, ethnopolitical processes and prospect of vernacular development of certain indigenous peoples.
Keywords: Siberia; ethnosocial processes; national policies; indigenous people; ethnocultural world